Situational effects of the school factors included in the dynamic model of educational effectiveness - Bert Creemers (South African Journal of Education, 2009)
We present results of a longitudinal study in which 50 schools, 113 classes and 2,542 Cypriot primary students participated. We tested the validity of the dynamic model of educational effectiveness and especially its assumption that the impact of school factors depends on the current situation of the school and on the type of problems/difficulties the school is facing. Reference is made to the methods used to test this assumption of the dynamic model by measuring school effectiveness in mathematics, Greek language, and religious education over two consecutive school years. The main findings are as follows. School factors were found to have situational effects. Specifically, the development of a school policy for teaching and the school evaluation of policy for teaching were found to have stronger effects in schools where the quality of teaching at classroom level was low. Moreover, time stability in the effectiveness status of schools was identified and thereby changes in the functioning of schools were found not to have a significant impact on changes in the effectiveness status of schools. Implications of the findings for the development of the dynamic model and suggestions for further research are presented.